2021
DOI: 10.3390/nano11010236
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Studies on Sustainable Synthesis of Gold Sol Displaying Dichroic Effect

Abstract: Gold nanoparticles depending on their shape and mixtures of multiple shapes can exhibit peculiar optical properties, including the dichroic effect typical of the Lycurgus cup, which has puzzled scientists for a long time. Such optical properties have been recently exploited in several fields such as paint technology, sensors, dichroic polarizers, display (LCD) devices, laser applications, solar cells and photothermal therapy among others. In this article, we have demonstrated a simple room temperature one-pot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…The dichroic effect is very rare; achieving and maintaining such special conditions in a solution requires very precise preparation. There are only a few works describing the dichroic effect of Ag and Au nanoparticles [ 27 , 28 ]. Dichroism is the result of the presence of the different shapes and sizes of nanoparticles in the colloids.…”
Section: Resultsmentioning
confidence: 99%
“…The dichroic effect is very rare; achieving and maintaining such special conditions in a solution requires very precise preparation. There are only a few works describing the dichroic effect of Ag and Au nanoparticles [ 27 , 28 ]. Dichroism is the result of the presence of the different shapes and sizes of nanoparticles in the colloids.…”
Section: Resultsmentioning
confidence: 99%
“…Dekker et al studied the dichroic solutions Ag and Au and showed that polydisperse asymmetric nanoparticles were present in all of them [5]. The dichroic effect was observed in AuNPs colloids by Koolo et al and Jakhmola, and both found asymmetric nanoparticles in dichroic colloids [31][32][33]. This leads to the conclusion that the polydispersity and asymmetric shape of the nanoparticles is the main reason for the dichroic behavior.…”
Section: Uv-vis Spectroscopymentioning
confidence: 99%
“…Because the LSPR properties depend heavily on the size and shape of these nanocrystals, it is highly desirable to achieve customizable sizes and shapes toward tunable LSPR bands in the UV–visible near infrared (NIR) region, according to the needs of applications. To date, significant efforts have been devoted to the shape control of Ag and Au nanocrystals, leading to the convenient availability of nanocrystals with diverse shapes, such as spheres [ 12 , 13 ], polyhedra [ 14 , 15 , 16 ], bipyramids [ 17 , 18 ], rods [ 1 , 19 , 20 ], wires [ 21 , 22 ], and plates [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. However, the synthesizing of nanocrystals with specific shapes, e.g., thin Au nanoplates, still needs substantial perfecting in terms of the morphological yield and size controllability.…”
Section: Introductionmentioning
confidence: 99%